Determination of Role Conflict and Role Ambiguity on Burnout with Cyberloafing as a Moderating Variable: Study on Generation Z Workers in Kediri Regency - Dian Shevira Putri; Udik Jatmiko; Diana Ambarwati (UPT Jurnal & Publikasi Ilmiah SPs Universitas Ibn Khaldun Bogor, 2025)
Burnout is a factor that can diminish employees' effectiveness in performing their tasks. This research intends to investigate the influence of role conflict and role ambiguity on burnout, with cyberloafing as a moderating variable. The research employs a quantitative method using purposive sampling. The population consists of Generation Z employees in Kediri Regency, aged 18 to 27 years. Data were collected through a survey completed by 100 Generation Z workers. Data analysis was conducted using smartPLS4.0. The results of this research is indicate a significant and positive relationship between role conflict and burnout, while role ambiguity does not have a significant effect on burnout. Cyberloafing has a significant moderating effect on the relationship between role conflict and role ambiguity on burnout. There-fore, it is recommended that companies clarify job roles, improve communication, and implement flexible cyberloafing policies to address role conflict, role ambiguity, burnout, and cyberloafing among Generation Z employees. Additionally, it is important to provide stress management training and create a supportive work environment. Employees are also encouraged to be proactive in communicating their needs and enhancing their skills. Future re-search should involve a larger sample size and additional varia-bles for more comprehensive results.